Review of the literature on models or frameworks for implementation of digital transformation processes - Torres, Alex A. (2024)
The objective of this document is to provide state-of- the-art information on models or frameworks for the implementation of digital transformation processes in organizations, with an emphasis on actions and initiatives in the higher education sector, and to propose avenues for future research. . To this end, a systematic review of the literature was carried out, where 202 articles were analyzed applying the procedure defined by Petersen as a methodology. The preliminary findings made it possible to identify seven (7) common components regarding the definition of digital transformation according to the authors. Likewise, few validated models or frameworks were evident in higher education scenarios to implement digital transformation processes in higher education institutions, higher education. Likewise, the contribution of a collaborative model and digital maturity in universities was not identified, which allows inferring about some knowledge gaps that persist or problems that have not yet been resolved, providing future work opportunities to make a contribution in this area, of the science.